Looking Back, Looking Forward: Examining the Processing of Abortion Experiences Using Public Abortion Narratives. Issue 2 (May 2021) - Swan, Laura E. T.; Rouland, Rebecca S.; Sperlich, Mickey; Ely, Gretchen E.; Walters, Connor
Limited research has utilized public abortion narratives to understand how individuals process through their abortion experiences. To address this gap in the literature, this study used thematic analysis to consider the public abortion stories of 39 participants from the Tennessee Stories Project, focusing on how individuals process through these experiences and the context of the abortion experience in a person's life course. Participants were primarily those who were abortion patients; however, abortion providers and supporters including partners or spouses, family members, and friends of those who received abortion care were also represented. Data analysis indicated that abortion seekers engage in introspection, involving political and religious/spiritual considerations; report specific feelings about their abortion experience, including having no regrets and feeling gratitude; process emotions related to the abortion experience by normalizing emotional responses and using mementos; and position their abortion in the context of their life, both in terms of their family and career opportunities and personal development. These findings provide valuable insight into how individuals process through the abortion experience, before, during, and after the abortion procedure, and suggest possible directions for service providers, advocates, and policy makers in order to better support abortion patients, providers, and family members.